Contingent Keynesianism: the IMF's model answer to the post-crash fiscal policy efficacy question in advanced economies. Issue 6 (2nd November 2019) - Clift, Ben
Abstract: Belying the International Monetary Fund's (IMF's) reputation as a bastion of neo-liberal policy orthodoxy, this article analyses important yet contingent transformations in IMF fiscal policy thinking which constituted a key intervention in international austerity debates. Applying only to advanced economies, and in the specific post-crash conditions, the Fund came to champion fiscal policy as a more potent and effective counter-cyclical tool. Analysis focuses on alterations to modeling assumptions and analytical techniques, beginning before the crash but accelerating after it, which intellectually bolstered this view. It finds the Fund's rediscovery of some older (Keynesian) assumptions was both longer in germination and more enduring than some have recognized. It also charts the reconciliation of this contingent Keynesianism to 'congenital' IMF concerns for fiscal sustainability. It highlights the variety of economic insights, often with vastly differing policy implications, found within the Fund, and indeed within mainstream macroeconomics. It builds on work questioning the stability, consistency, and coherence of economic ideas suggested by the paradigm framework, and identifies limitations of a paradigm lens for understanding incremental IMF ideational change. It contributes to politics of economic ideas scholarship in highlighting the importance of economic method and modeling assumptions as sites of contestation within gradual but meaningful ideational change.